An explorative study on the antimicrobial effects and mechanical properties of 3D printed PLA and TPU surfaces loaded with Ag and Cu against nosocomial and foodborne pathogens. (January 2023) - Εkonomou, Sotiriοs Ι.; Soe, Shwe; Stratakos, Alexandros Ch.
Abstract: Antimicrobial 3D printed surfaces made of PLA and TPU polymers loaded with copper (Cu), and silver (Ag) nanoparticles (NPs) were developed via fused deposition modeling (FDM). The potential antimicrobial effect of the 3D printed surfaces against Escherichia coli, Listeria monocytogenes, Salmonella Typhimurium, and Staphylococcus aureus was evaluated. Furthermore, the mechanical characteristics, including surface topology and morphology, tensile test of specimens manufactured in three different orientations (XY, XZ, and ZX), water absorption capacity, and surface wettability were also assessed. The results showed that both Cu and Ag-loaded 3D printed surfaces displayed a higher inhibitory effect against S. aureus and L. monocytogenes biofilms compared to S. Typhimurium and E. coli biofilms . The results of SEM analysis revealed a low void fraction for the TPU and no voids for the PLA samples achieved through optimization and the small height (0.1 mm) of the printed layers. The best performing specimen in terms of its tensile was XY, followed by ZX and XZ orientation, while it indicated that Cu and Ag-loaded material had a slightly stiffer response than plain PLA. Additionally, Cu and Ag-loaded 3D printed surfaces revealed the highest hydrophobicity compared to the plain polymers making them excellent candidates for biomedical and food production settings to prevent initial bacterial colonization. The approach taken in the current study offers new insights for developing antimicrobial 3D printed surfaces and equipment to enable their application towards the inhibition of the most common nosocomial and foodborne pathogens and reduce the risk of cross-contamination and disease outbreaks. Graphical abstract: Image 1 Highlights: Low void fraction for TPU and no voids for PLA with or without metal alloys. 3D printed PLA, and TPU surfaces with Cu and Ag revealed low surface wettability. The tensile test showed that XZ printed structures had lower stiffness than XY and ZX. PLA-Cu and TPU-Cu surfaces inhibited the growth of S. aureus and L. monocytogenes . The highest inhibitory effect for all pathogens was seen on PLA and TPU-Ag surfaces.